2020
DOI: 10.3390/microorganisms8091429
|View full text |Cite
|
Sign up to set email alerts
|

Viral Abundance and Diversity of Production Fluids in Oil Reservoirs

Abstract: Viruses are widely distributed in various ecosystems and have important impacts on microbial evolution, community structure and function and nutrient cycling in the environment. Viral abundance, diversity and distribution are important for a better understanding of ecosystem functioning and have often been investigated in marine, soil, and other environments. Though microbes have proven useful in oil recovery under extreme conditions, little is known about virus community dynamics in such systems. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…A meta-analysis of eight production wells indicated that the abundance of viruses is approximately 3 × 10 8 mL −1 . Viral abundance of production wells during water flooding is higher than that in production wells during microbial flooding 31 . In addition, previous study uncovered that viruses are widespread in hydraulically fractured wells, rivalling the viral abundance observed in peatland soil ecosystems 33 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A meta-analysis of eight production wells indicated that the abundance of viruses is approximately 3 × 10 8 mL −1 . Viral abundance of production wells during water flooding is higher than that in production wells during microbial flooding 31 . In addition, previous study uncovered that viruses are widespread in hydraulically fractured wells, rivalling the viral abundance observed in peatland soil ecosystems 33 .…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, viruses actively regulate and rebuild host metabolism by deploying auxiliary metabolic genes (AMGs) during infection. Recent studies have uncovered the presence of a substantial number of viruses within the oil reservoir environment 31,32 . A meta-analysis of eight production wells indicated that the abundance of viruses is approximately 3 × 10 8 mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…They can thrive at temperature ranges between −12 and 96°C ( Munson-Mcgee et al, 2018 ), pH values from 1 to 11 (at the least), saturated salinity ( Pietilä et al, 2013 ), and extreme dryness ( Gil et al, 2021 ). According to this, viruses have been found in hydrothermal vents ( Russell and Hall, 1997 ), including those located at great depths in the oceans ( Thomas et al, 2021 ), in oil fields ( Zheng et al, 2020 ), in the soils of hyper-arid deserts ( Zablocki et al, 2015 ), at hundreds of meters in the subsurface ( Daly et al, 2019 ), or in places with salt concentrations far above the optimal for most living beings ( Santos et al, 2012 ). Many of these locations share environmental characteristics that also occur in extraterrestrial environments.…”
Section: Viruses At the Planetary Scale: The Virospherementioning
confidence: 99%
“…Research over the past three decades has firmly established that viruses are the most abundant and diverse biological entities (Bratbak & Heldal, 2000;Wommack & Colwell, 2000;Weinbauer, 2004), thereby forming an integral component of microbial food web (viruses, bacteria, picophytoplankton, protozoa) in a great variety of aquatic environments (Bratbak et al, 1994;Clasen et al, 2008;Wilhelm & Matteson, 2008). Viral lysis plays fundamental roles in cycling nutrients and organic matter (Middelboe et al, 2008;Staniewsski & Short, 2014), structuring the microbial food web dynamics and regulating carbon flow (Fuhrman, 1999;Bouvy et al, 2011;Breitbart, 2012), governing microbial diversity (Weinbauer & Rassoulzadegan, 2004;Keshri et al, 2017;Zheng et al, 2020). Bacteriophages prevail in virioplankton in many aquatic ecosystems, including reservoirs (Peduzzi & Schiemer, 2004;Ram et al, 2005;Sime-Ngando, 2014;Hanson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%